The Scatopsidae (Diptera) of Sardinia, with description of a new species - Haenni, Jean-Paul (Zootaxa, 2009)
Eleven species of the family Scatopsidae are reported from Sardinia, 10 of which for the first time, from collections made in the Marganai area (Carbonia-Iglesias province) and some additional material. Swammerdamella spinigera sp. nov., closely related to S. pediculata (Duda, 1928), is described and figured. The state of knowledge of the Sardinian fauna and its affinities are discussed.